The economic status of parents and family food security as a risk factor for stunting in children under five years old in Bejiharjo Village - Ulfa Malika Putri Raharja; Waryana Waryana; Almira Sitasari (Ilmu Gizi Indonesia, 2019)
Background: The prevalence of stunting among children under five years old in Gunungkidul Regency are 27.9%, and in the Karangmojo II Community Health Center work area are 30.25% or 337 children under five years old. Stunting that occurs in children under five years old can have an impact on decreasing productivity, increasing the risk of degenerative diseases, decreasing intelligence, and increasing the birth of babies with low birth weight in the future. Objective: To examine the risk factors of parents' economic status and family food security against the incidence of stunting in children under five years old  in Bejiharjo Village. Methods: The type of research was an analytical (observational) survey with a case-control study approach. The subjects of this study were children aged 24−59 months. This research was conducted on February 2019. The sampling technique used to determine the area was purposive sampling, and to determine the sample was simple random sampling. The research instruments used were economic and family food security questionnaires. One hundred forty-one children under five years old became the subject in this study. Data were analyzed by using Chi-Square analysis. Results: Bivariate analysis showed economic status of parents (p=0.002; OR=3.182) and family food security (p=0.007; OR=3.164) were risk factor for stunting in children under five years old in Bejiharjo Village. Conclusion: The economic status of parents and family food security act as risk factor for stunting in infants in Bejiharjo Village